Immigration and entrepreneurship in the United States - Pierre Azoulay; Benjamin F. Jones; J. Daniel Kim; Javier Miranda (Friedrich Schiller University Jena, 2021)
Immigrants can expand labor supply and compete for jobs with native-born workers. But immigrants may also start new firms, expanding labor demand. This paper uses U.S. administrative data and other data sources to study the role of immigrants in entrepreneurship. We ask how often immigrants start companies, how many jobs these firms create, and how firms founded by native-born individuals compare. A simple model provides a measurement framework for addressing the dual roles of immigrants as founders and workers. The findings suggest that immigrants act more as "job creators" than "job takers" and play outsized roles in U.S. high- growth entrepreneurship.
Keywords: 330; Migranten; Arbeitsmigranten; Unternehmen; Unternehmensgründung; USA